Cover Picture: Phys. Status Solidi C 2/2013. Issue 2 (14th February 2013) - Stanek, Christopher R.; Nikl, Martin; Kovács, László; Greulich‐Weber, Siegmund
<x xml:space="preserve">Abstract</x> Sol‐gel methods allow monodisperse growth of ZnO crystals from nano to micro scale. The known strong surface conductivity upon UV illumination competes with volume conductivity achieved by semiconductor doping or by intrinsic defects. In their paper on pp. 221–226, Greulich‐Weber, Azam, Brodehl, and Baumgarten correlate microwave conductivity measurements of nano and micro crystalline ZnO with studies of the microscopic structure of defects by electron paramagnetic resonance investigations. The cover page shows examples of monodisperse sol‐gel ZnO crystals and the electromagnetic field distribution in a specially developed microwave resonator for powder conductivity measurements. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>